Mesoporous Silica-Layered Gold Nanorod Core@Silver Shell Nanostructures for Intracellular SERS Imaging and Phototherapy - Sun-Hwa Seo; Ara Joe; Hyo-Won Han; Panchanathan Manivasagan; Eue-Soon Jang (MDPI AG, 2024)
Precision diagnosis-guided efficient treatment is crucial to extending the lives of cancer patients. The integration of surface-enhanced Raman scattering (SERS) imaging and phototherapy into a single nanoplatform has been considered a more accurate diagnosis and treatment strategy for cancer nanotheranostics. Herein, we constructed a new type of mesoporous silica-layered gold nanorod core@silver shell nanostructures loaded with methylene blue (GNR@Ag@mSiO2-MB) as a multifunctional nanotheranostic agent for intracellular SERS imaging and phototherapy. The synthesized GNR@Ag@mSiO2-MB nanostructures possessed a uniform core-shell structure, strong near-infrared (NIR) absorbance, photothermal conversion efficiency (65%), dye loading ability, SERS signal, and Raman stability under phototherapy conditions. Under single 785 nm NIR laser irradiation, the intracellular GNR@Ag@mSiO2-MB nanostructures were dramatically decreased to <9%, which showed excellent photothermal and photodynamic effects toward cancer cell killing, indicating that the combination of photothermal therapy (PTT) and photodynamic therapy (PDT) of the GNR@Ag@mSiO2-MB nanostructures could greatly enhance the therapeutic efficacy of cancer cell death. GNR@Ag@mSiO2-MB nanostructures demonstrated a strong Raman signal at 450 and 502 cm−1, corresponding to the δ(C-N-C) mode, suggesting that the Raman bands of GNR@Ag@mSiO2-MB nanostructures were more efficient to detect CT-26 cell SERS imaging with high specificity. Our results indicate that GNR@Ag@mSiO2-MB nanostructures offer an excellent multifunctional nanotheranostic platform for SERS imaging and synergistic anticancer phototherapy in the future.